Dust Aerosol’s Deposition and its Effects on Chlorophyll-A Concentrations Based on Multi-Sensor Satellite Observations and Model Simulations: A Case Study - Wang, Wencai; He, Zhizheng; Hai, Shangfei; Sheng, Lifang; Han, Yongqing; Zhou, Yang (Frontiers in Environmental Science, 2022)
Asian dust deposition is an important source of nutrients to the Pacific Ocean, when aerosol dust is deposited into the ocean, it will affect the biological productivity and hence climate. In this paper, we analyzed a dust process that occurred in the Taklimakan Desert during 21–25 May 2019 by employing multi-sensor satellite observations and the WRF-Chem model. It is found that dust aerosols rise in the Taklimakan Desert, moving eastward at high altitudes under the role of the westerly winds, passing over the downwind regions, and deposition in the Pacific Ocean. Dust aerosol deposition results in an increase of chlorophyll-a (Chl-a) concentrations and particulate organic carbon (POC) after 2 days, Chl-a concentrations and POC increase by 175 and 873%, respectively. Moreover, the values of Chl-a concentrations and POC are 256 and 644% higher than the 5-years average during the same period.